2010
DOI: 10.1002/bit.22608
|View full text |Cite
|
Sign up to set email alerts
|

A multichamber fluidic device for 3D cultures under interstitial flow with live imaging: Development, characterization, and applications

Abstract: Interstitial flow is an important biophysical cue that can affect capillary morphogenesis, tumor cell migration, and fibroblast remodeling of the extracellular matrix, among others. Current models that incorporate interstitial flow and that are suitable for live imaging lack the ability to perform multiple simultaneous experiments, for example, to compare effects of growth factors, extracellular matrix composition, etc. We present a nine-chamber radial flow device that allows simultaneous 3D fluidic experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…Differences in geometrical configurations of perfusion bioreactor systems and the complex internal architecture of scaffolds (Bancroft et al, 2002;Bonvin et al, 2010;Wendt et al, 2003;Zhao and Ma, 2005) makes correlating observed biological outcomes on the basis of inlet fluid flow-rate very difficult. Calculation of the  within systems allows comparisons to be made on a single representative scale.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in geometrical configurations of perfusion bioreactor systems and the complex internal architecture of scaffolds (Bancroft et al, 2002;Bonvin et al, 2010;Wendt et al, 2003;Zhao and Ma, 2005) makes correlating observed biological outcomes on the basis of inlet fluid flow-rate very difficult. Calculation of the  within systems allows comparisons to be made on a single representative scale.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous bioreactor types have been designed for 3D tissue engineering applications and their roles have been reviewed by Martin et al, 47 spinner flasks, rotating wall bioreactors, hollow fiber membrane systems, and perfusion rigs being the most common. Several perfusion bioreactor styles have been devised to date 43,[48][49][50][51] ( Fig. 1).…”
Section: Fluid Shear Stress and Mechanotransduction In Two-dimensionamentioning
confidence: 99%
“…28 While it is possible to control the concentrations of exogenous factors such as insulin, it is difficult to control the gradients of autocrine factors in the presence of significant flow. [29][30][31] A two-compartment microfluidic device ͑Fig. 1͒, in which the cell culture region is separated from a high-flow channel by a semipermeable membrane, offers the possibility of uncoupling oxygen and molecular transport from the shear stress imparted to the cells.…”
Section: Introductionmentioning
confidence: 99%